ARPOT: an Augmented Reality Platform for Outdoor Teaching - Selzer, Matias Nicolas (2021)
In the last years, there has been interest in introducingAugmented Reality (AR) into education. However, users who arenot technical specialists require tools to facilitate the creation andcustomisation of AR experiences. Since educational tours and excursionsconnect students with the concepts taught in classroom, and ARincreases the students? interest and motivation, we developed ARPOT,an AR platform for outdoor teaching that integrates tools for the teacherto easily create AR content and tools for students to view and interactwith such AR content without internet connection. ARPOT was testedby 240 students of different educational levels at the wetlands of Villa delMar, Argentina, and 12 new students at the campus of our university. Inboth case studies, the students reported a more motivating and engagingexperience, and the educators reported that ARPOT was a powerful toolfor content creation.